2014
DOI: 10.1111/cns.12201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Polymorphisms Involved in the Hypothalamic–Pituitary–Adrenal Axis and their Interactions with Environmental Factors on Antidepressant Response

Abstract: Our results support a definite role for CRHR1 in the pharmacogenetics of antidepressant drugs. This may contribute to interpatient differences in their responses to antidepressant drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…Polymorphism rs352428 worsens the response to antidepressant treatment in Caucasians [36]. Interestingly, polymorphisms rs1360780 and rs3800373 were found to have an association with improved outcomes from antidepressant treatment in Caucasian populations in meta-analysis [30], but there was no significant association in an Asian population [37] although the frequency of these alleles is similar in both populations. Lekman et al [38] also found an association of rs4713916 with remission with citalopram treatment in the Caucasian population [38].…”
Section: Fkbp5 and The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…Polymorphism rs352428 worsens the response to antidepressant treatment in Caucasians [36]. Interestingly, polymorphisms rs1360780 and rs3800373 were found to have an association with improved outcomes from antidepressant treatment in Caucasian populations in meta-analysis [30], but there was no significant association in an Asian population [37] although the frequency of these alleles is similar in both populations. Lekman et al [38] also found an association of rs4713916 with remission with citalopram treatment in the Caucasian population [38].…”
Section: Fkbp5 and The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…Similarly, Perlis et al (2009) did not report any significant findings in terms of the same SNP and responder or remission status in Caucasian patients who were administered duloxetine over the course of 6 weeks. Geng et al (2014) also did not find any link between the same SNP and response to 8 weeks of treatment with different SSRIs and SNRIs in their Chinese sample.…”
Section: Polymorphisms In Genes Related To the Arginine Vasopressin (mentioning
confidence: 77%
“…greater serum ACTH concentrations. In addition, Geng et al (2014) found a SNP (rs28364032) and related haplotypes within CRHR1 to predict remission after administering various SSRIs and SNRIs, and Chang et al (2015b) found a haplotype within POMC to predict remission status after treatment with escitalopram or mirtazapine. Notably, studies reporting positive findings in terms of the CRH and melanocortin system had a much higher average quality score (7.3 out of 14) when compared to those reporting null-findings (4.5 out of 14), which highlights the need for further research adhering to high standards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations